Diffusion process control with use of recommendation-forming system - Sidletskyi, Victor (My University, 2013)
Removing sugar from beet chips is one of the key processes of sugar production, which largely affects the cost of production, the cost of energy and loss of sugar. Despite the relatively simple flow sheet, process is a complex system where a variety of physical, chemical and biological processes take place.
Keywords: fuzzy logic; algorithms of logical output; technological control process; transport problem; game theory; structural analysis; functional structure; knowledge base; нечітка логіка; алгоритми; технологічний процес управління; логічного виведення; теорія ігор; структурний аналіз; функціональна структура; база знань; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка